Design of QR Code Technology in MC Swimming Pool Website Design to Improve User Experience and Operational Efficiency - Syahputra, Mhd Rinaldi; Perwitasari, Ika Devi (International Journal of Computer and Information System (IJCIS), 2024)
QR Code which is an abbreviation of Quick Response Code, QR Code is in the form of a square box, similar to a barcode, but with a more detailed appearance. The use of QR Code Technology in this research serves to facilitate identification and confirmation of entrance tickets for swimming pool visitors increase the speed and easy to buy a ticket. The research methodology used in system design is waterfall method. The waterfall method displays simple processes that do not overlap with the SDLC (system development life cycle) model.The programming language used is PHP, with the implementation of the CodeIgniter 3 Framework, and MySQL as the Database management system.The problem that often occurs is when the queue of visitors enters on holidays or days when there are lots of visitors causing long queues and less efficiency in ticket sales operations and the process of entering visitors to the swimming pool.This research aims to improve the user's operational system in ordering tickets which must initially be done come directly to the swimming pool location and in the new system visitors can purchase tickets online and operational efficiency of the MC Swimming Pool through the application of QR Code technology on the website, it makes the process of checking ticket data easier so that visitors can enter the swimming pool area The result of this research is to create an information system plan that allows users to order tickets online and visitors can enter the swimming pool area quickly and easily using a QR code as a visitor entry ticket.